MNCs as dispersed structures of power: Performance and management implications of power distribution in the subsidiary portfolio - Lee, Jong Min (Journal of International Business Studies, 2022)
Multinational corporations (MNCs) are considered as dispersed structures of power, in which diverse headquarters (HQ)–subsidiary power relationships collectively influence performance and management. Yet, few studies have accounted for the subsidiary portfolio characteristics shaped by the entire set of differentiated HQ–subsidiary power relationships, and little is known about their effect on the performance and management decisions of MNCs. Drawing on agency and resource dependence theories, this study investigates how the power structure of the MNC, or the pattern of power distribution in the subsidiary portfolio, affects MNC performance and expatriate utilization. Results from a comprehensive panel of Korean MNCs show that the degree of power concentration in the subsidiary portfolio has inverted U-shaped relationships with MNC performance and the use of expatriate control. However, the results also reveal that these relationships vary between manufacturing and downstream subsidiary portfolios. These findings suggest that the structural characteristics of the subsidiary portfolio are important determinants of MNC performance and management. This study opens an important new avenue for international business scholarship by explicitly conceptualizing the MNC as a portfolio of differentiated subsidiaries and by examining the consequences of the subsidiary portfolio characteristics.